First report of Papaya ringspot virus infecting Carica papaya In Argentina - Cabrera Mederos, Dariel (2016)
Papaya plants (Carica papaya L.) with severe leaf mosaic and deformation symptoms were observed and collected in the Formosa, Corrientes and Misiones provinces of northern Argentina. These symptoms were similar to those induced by Papaya ringspot virus (PRSV-P) (Tripathi et al., 2008). Electron microscopy observations of leaf dip preparations from symptomatic papaya leaves revealed typical flexuous potyvirus particles of ca. 800×12nm (Francki et al., 1985). Papaya leaf extracts from affected plants were mechanically inoculated on healthy papaya plants, which showed typical symptoms of the disease. The presence of the virus in symptomatic plants was tested and confirmed by double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA), using a specific PRSV antiserum (Agdia, Elkhart, IN). Total RNA was extracted using RNeasy Plant Mini Kit (Qiagen, Hilden, Germany) and tested by reverse transcription-polymerase chain reaction (RT-PCR) with specific PRSV coat protein gene primers: BoCP_Fwd 5’-TCCAAGAATGAAGCTGTGGACGCTGGTT-3’ and BoCP_Rev 5’-TYAGTTGCGCATACCCAGGAGAGAGT-3’. The RT-PCR amplicons of the expected size were purified and directly sequenced in both directions at Macrogen Inc. (Seoul, Korea). BLASTn analysis of the sequenced fragments (828bp) (GenBank accession Nos. KX385113 to KX385116) showed 97 to 98% nucleotide sequence identity with previously reported PRSV-P isolates from Brazil (AF344642, JQ755427, JQ755424). To the best of our knowledge, this is the first report of the occurrence of PRSV in papaya plants in Argentina. Due to the devastating effects of PRSV in papaya (Tripathi et al., 2008) and the recent increase of cultivation area in northern Argentina, it becomes necessary to implement management strategies to control this disease and avoid the introduction of the virus into new production areas.